Valuation of Tencent Holdings Ltd. - Xiaoxiao Ji (2022)
Tencent and Facebook, the two social media behemoths, occupied prominent roles in the technology media in 2017. Tencent has surpassed Facebook in terms of market capitalization for the first time, making it the world's fifth biggest corporation by market capitalisation, after only Apple, Alphabet, Microsoft, and Amazon. Tencent's stock price has increased by more than 40% since the beginning of 2020, owing to the favourable epidemic situation and the catalysis of its explosive games. As a result, Tencent's market capitalization has surpassed that of Facebook, making it the world's most well-known social media company for the second time. Aiming to give a helpful investment recommendation, this thesis focuses on the development trend of Tencent, and the company's future prospects.